Malignant solitary fibrous tumors of the left atrial endocardium. (February 2022) - Suzuki, Yamato; Matsuda, Yasushi; Saito, Ryoko; Adachi, Osamu; Okada, Yoshinori
Solitary fibrous tumors are typically benign and usually develop in the pleura. We herein report the first case of a solitary fibrous tumor that was pathologically malignant and developed in the left atrial endocardium. A 24-year-old woman underwent resection of a malignant solitary fibrous tumor in her right forearm at another hospital. Computed tomography demonstrated a mass in her right pleura 2 months after the surgery. She was referred to our hospital, and a tumor in her left atrium was subsequently found. She underwent resection of these tumors, and pathological examination showed that they were both malignant solitary fibrous tumors.